FACTORS AFFECTING LQ45 COMPANY VALUES IN 2016-2018 - Kusumawati, Hanifa Wanda; Astanto, Jarot Hari; S, Yuli Chomsatu (Common Publisher, 2020)
The purpose of this study is to examine the effect of leverage, company size, company structure, liquidity, and profitability on LQ45 firm value. The population that is the object of this research is the stock market index companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. The total population in this study were 45 companies, this study was obtained from purposive sampling which then produced a sample of 23 companies for further research. The analysis technique used is multiple linear regression analysis. Calculations in research data using the SPSS version 22 program. Based on data analysis and discussion, it can be concluded that leverage, company structure, liquidity, and profitability have a negative effect on firm value. While the size of the company has a significant effect on firm value.